Improve the Photovoltaic Performing of Carbon-Form Perovskite Solar Cells (International Journal of Innovative Research in Computer Science & Technology, 2022)
A solvent-assisted approach was  established to make CH3NH3PbI3 perovskite absorber  layers. A mixture of CH3NH3I, PbI2, c-butyrolactone, and  dimethyl sulfoxide (DMSO) was used, followed by the  addition of chlorobenzene (CB). The approach produced  ultra-flat and dense perovskite capping layers atop  mesoporous films TiO2, allowing for a significant boost in  the performance of carbon electrode-form perovskite solar  cells using free whole transport material (HTM) (PSCs). As  a comparative solvent, toluene (TO) was also investigated.  The generated HTM-free PSCs form on drop-casting CB  showed a power conversion efficiency (PCE) of 9.73  percent at an annealing temperature of 100 C, which is 36  and 71 percent greater than those fabricated from perovskite  films using TO or without adding an additional solvent,  respectively. The interaction between the intermediate  phase of PbI2–DMSO–CH3NH3I and the extra solvent was  discussed. The effect of annealing temperature on absorber  film development, morphology, and crystalline structure  was also examined, and the results were connected with  photovoltaic performance. Highly efficient, simple, and  stable HTM-free solar cells with a PCE of 11.44 percent  were created using the best perovskite absorbers annealed at  120 C.
Keywords: Perovskite; Solar Cells; Carbon Form; Photovoltaic; Spin coating